Pembuatan Video sebagai Sarana Promosi Perpustakaan di Dinas Kearsipan dan Perpustakaan Kabupaten Pesisir Selatan - Danisa Puji Astuti; Desriyeni Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractThe research method used in this paper is qualitative method used direct observation and interviews with Head of Library and Librarian in the Archives and Library of Pesisir Selatan Regency. Based on data analyzing the data can be concluded that the steps in making video promotion library as follows : First, pre production is the initial stage before the implementation of video production consisting of the discovery of ideas, synopsis, treatment, storyboard, shotting script, production planning and production preparation. Second step is, production to realize all the steps that exist in pre production stage. And third step is, post production is the final stage in video production before the video is ready to be presented.Keywords: promotion video, library.